RANCANG BANGUN KONTROL KADAR AMONIA DAN PH AIR BERBASIS ARDUINO PADA BUDIDAYA IKAN - Dimasanggie Elul Talanta (Otopro, 2021)
In the fish pond ecosystem there are various factors that can inhibit fish growth or even kill fish,  one of which is the water factor,  the water itself has various factors,  one of which is the quality of PH levels and amonia levels. Therefore,  this paper discusses the design and manufacture of a control device for PH levels and amonia levels to make it easier for farmers to check PH levels and amonia levels in the pond. This control device uses a DFROBOT V.2 sensor as a PH sensor and a DS18B20 sensor as a temperature sensor as well as an Arduino UNO controller. The method used to control amonia is by comparing the data from PH and the temperature in the pool water,  this tool will work if the amonia level is higher. from 0.8ppm by activating the aerator to keep the amonia in the pool water normal. Meanwhile,  to maintain the PH of the water more than 6 and less than 7,  it is necessary to add pond water by activating the water pump. The results of this study can be used as a reference for future research for the development of Arduino Uno-based PH and amonia level control devices.